The association between high risk of sleep apnea, comorbidities, and risk of COVID-19: a population-based international harmonized study - Chung, Frances (Sleep Breath, 2021)
PURPOSE: Obstructive sleep apnea (OSA) may increase the risk of severe COVID-19; however, the level of potential modulation has not yet been established. The objective of the study was to determine the association between high risk of OSA, comorbidities, and increased risk for COVID-19, hospitalization, and intensive care unit (ICU) treatment. METHODS: We conducted a cross-sectional population-based web survey in adults in 14 countries/regions. The survey included sociodemographic variables and comorbidities. Participants were asked questions about COVID-19, hospitalization, and ICU treatment. Standardized questionnaire (STOP questionnaire for high risk of OSA) was included. Multivariable logistic regression was conducted adjusting for various factors. RESULTS: Out of 26,539 respondents, 20,598 (35.4% male) completed the survey. Mean age and BMI of participants were 41.5 ± 16.0 years and 24.0 ± 5.0 kg/m(2), respectively. The prevalence of physician-diagnosed OSA was 4.1% and high risk of OSA was 9.5%. We found that high risk of OSA (adjusted odds ratio (aOR) 1.72, 95% confidence interval (CI): 1.20, 2.47) and diabetes (aOR 2.07, 95% CI: 1.23, 3.48) were associated with reporting of a COVID-19 diagnosis. High risk for OSA (aOR 2.11, 95% CI: 1.10–4.01), being male (aOR: 2.82, 95% CI: 1.55–5.12), having diabetes (aOR: 3.93, 95% CI: 1.70–9.12), and having depression (aOR: 2.33, 95% CI: 1.15–4.77) were associated with increased risk of hospitalization or ICU treatment. CONCLUSIONS: Participants at high risk of OSA had increased odds of having COVID-19 and were two times more likely to be hospitalized or treated in ICU. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11325-021-02373-5.